Analysis of Early Childhood Pre-Service Teacher's Science Concepts Comprehension Based On Their Science Process Skill - Ni Luh Putu Nina Sriwarthini; Baik Nilawati Astini; Gunawan Gunawan (Jurnal Penelitian Pendidikan IPA, 2023)
Science concepts comprehension is a foundation that allows students to create thinking constructions to another related concept or more complex concepts, facts, laws, principles, and theories in science. Understanding the concept of science is one of the important things required by early childhood education pre-service teachers as professional and competent educators in their fields. This research is an ex-post-facto research, with the aim of analyzing science concepts comprehension based on science process skills of the early childhood education pre-service teachers, especially on the subjects of the diversity of living things and environmental pollution. The subjects in this study were early childhood education students in semester VI of the 2021/2022 academic year. Analysis of science concept comprehension was carried out using the Certainty of Response Index (CRI) method. The results showed: 1) The Comprehension of Science concepts of early childhood education pre-service teachers with the criteria of understanding the concept (PK) is at 81.75%, not understanding the concept (TPK) at 4,90%, and misconceptions (M) at 13.34%; 2) The comprehension of science concept of early childhood education pre-service teachers based on high category science process skills are better than the science concept comprehension of early childhood education pre-service teachers with low category science process skills. The data obtained confirm that the comprehension of science concepts in early childhood education pre-service teachers is high. The comprehension of science concepts that owned by early childhood education pre-service teachers is directly proportional to their science process skills, the higher the science process skills of early childhood education pre-service teachers, the higher their science concepts comprehension.